Synthesis of a Novel Magnetic Biochar from Lemon Peels via Impregnation-Pyrolysis for the Removal of Methyl Orange from Wastewater - Samah Daffalla; Enshirah Da’na; Amel Taha; Mohamed R. El-Aassar (Magnetochemistry)
This research examined the elimination of methyl orange (MO) utilizing a novel magnetic biochar adsorbent (MLPB) derived from lemon peels via an impregnation-pyrolysis method. Material characterization was conducted using SEM, XRD, TGA, FTIR, and nitrogen adsorption isotherms. SEM-EDX analysis indicates that MLPB is a homogeneous and porous composite comprising Fe, O, and C, with iron oxide uniformly dispersed throughout the material. Also, MLPB is porous with an average pore diameter of 4.65 nm and surface area value (111.45 m2/g). This study evaluated pH, MO concentration, and contact time to analyze the adsorption process, kinetics, and isothermal behavior. Under optimal conditions, MLPB was able to remove MO dye from aqueous solutions with an efficiency of 90.87%. Results showed optimal MO removal at pH 4, suggesting a favorable electrostatic interaction between the adsorbent and dye. To ascertain the adsorption kinetics, the experimental findings were compared using several adsorption models, first- and second-orders, and intra-particle diffusion. According to the findings, the pseudo-second-order model described the adsorption kinetic promoting the formation of the chemisorption phase well. Modeling of intra-particle diffusion revealed that intra-particle diffusion is not the only rate-limiting step. A study involving isothermal systems showed that Langmuir is a good representation of experimental results; the maximum adsorption capacity of MLPB was 17.21 mg/g. According to the results, after four cycles of regeneration, the produced magnetic material regained more than 88% of its adsorption ability.